'Resistance is futile?' – paradoxical inhibitory effects of KATP channel closure in glucagon‐secreting α‐cells. (7th August 2020) - Zhang, Quan; Dou, Haiqiang; Rorsman, Patrik
Abstract: By secreting insulin and glucagon, the β‐ and α‐cells of the pancreatic islets play a central role in the regulation of systemic metabolism. Both cells are equipped with ATP‐regulated potassium (KATP ) channels that are regulated by the intracellular ATP/ADP ratio. In β‐cells, KATP channels are active at low (non‐insulin‐releasing) glucose concentrations. An increase in glucose leads to KATP channel closure, membrane depolarization and electrical activity that culminates in elevation of [Ca 2+ ]i and initiation of exocytosis of the insulin‐containing secretory granules. The α‐cells are also equipped with KATP channels but they are under strong tonic inhibition at low glucose, explaining why α‐cells are electrically active under hypoglycaemic conditions and generate large Na + ‐ and Ca 2+ ‐dependent action potentials. Closure of residual KATP channel activity leads to membrane depolarization and an increase in action potential firing but this stimulation of electrical activity is associated with inhibition rather than acceleration of glucagon secretion. This paradox arises because membrane depolarization reduces the amplitude of the action potentials by voltage‐dependent inactivation of the Na + channels involved in action potential generation. Exocytosis in α‐cells is tightly linked to the opening of voltage‐gated P/Q‐type Ca 2+ channels, the activation of which is steeply voltage‐dependent. Accordingly, the inhibitory effect of the reduced action potential amplitude exceeds the stimulatory effect resulting from the increased action potential frequency. These observations highlight a previously unrecognised role of the action potential amplitude as a key regulator of pancreatic islet hormone secretion. Abstract : Abstract figure legend The confocal images of a mouse pancreatic islet with β‐cells in red (top left), α‐cells in green (middle left) and merged image (bottom left). The images were taken at the top of an islet using an upright confocal microscope, which is why a clear separation of the β‐ and α‐cells is not as evident as in the centre of the islet. Panels to the right show the effects of KATP channel closure on electrical activity in β‐ (top right) and α‐cells (middle right). The schematic (lower right) summarizes the relationship between KATP channel closure/electrical activity on insulin and glucagon secretion. A decrease in KATP channel activity leads to a biphasic stimulation of insulin secretion (from a low basal value) but inhibition of glucagon secretion (from a high basal rate) despite similar effects on electrical activity in α‐ and β‐cells. This Topical Review discusses this paradox.